2019
DOI: 10.1249/mss.0000000000002112
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Modulates Gut Microbiota Profile and Improves Endotoxemia

Abstract: Introduction Intestinal metabolism and microbiota profiles are impaired in obesity and insulin resistance. Moreover, dysbiotic gut microbiota has been suggested to promote systemic low-grade inflammation and insulin resistance through the release of endotoxins particularly lipopolysaccharides. We have previously shown that exercise training improves intestinal metabolism in healthy men. To understand whether changes in intestinal metabolism interact with gut microbiota and its release of inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
191
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(245 citation statements)
references
References 50 publications
2
191
4
2
Order By: Relevance
“…Frequent treatment with antibiotics and/or a regular intake of non-antibiotic drugs have negative effects on the gut microbiota 33–35. Regular exercise and consuming a sport-specific diet are known to be associated with a favourable gut microbiota 36–38. Furthermore, the superdonor should not be a first-degree relative of any of the patients in a trial since the intestinal microbiota is affected by the genetic composition, and a superdonor and recipient with greater genetic similarity may also have greater similarities in their faecal microbiota 39 40.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent treatment with antibiotics and/or a regular intake of non-antibiotic drugs have negative effects on the gut microbiota 33–35. Regular exercise and consuming a sport-specific diet are known to be associated with a favourable gut microbiota 36–38. Furthermore, the superdonor should not be a first-degree relative of any of the patients in a trial since the intestinal microbiota is affected by the genetic composition, and a superdonor and recipient with greater genetic similarity may also have greater similarities in their faecal microbiota 39 40.…”
Section: Discussionmentioning
confidence: 99%
“…There might be numerous changes responsible for the improved metabolic phenotypes in both dams and offspring after maternal exercise. Given the pivotal role of gut microbiota plays in metabolic health and the confirmed link of exercise with the intestinal microbial community (Liu et al, 2020;Motiani et al, 2020), we discussed the potential contributions of gut microbiota to the intergenerational benefits of maternal exercise. Our data demonstrated that maternal exercise significantly modified gut microbiota in dams fed HFD at weaning, including both structure and composition, which was inconsistent with the results of another recent study.…”
Section: Discussionmentioning
confidence: 99%
“…Red and blue represent significant association determined by ANCOM after FDR correction for multiple comparisons at a significant level adj.P < 0.05. levels in our study. In prediabetes or diabetic humans, Blautia abundance was found to be associated with better whole-body insulin sensitivity and lower glucose uptake in the colon 35 . Additionally, we identified Akkermansia as higher in mice having above-median plasma cholesterol but was not significantly related to plasma glucose.…”
Section: Discussionmentioning
confidence: 98%